The Effect of Good Corporate Governance on Going Consensus Audit Opinions in Regional Public Companies Tirta Sumedang Medal - Nadia Nurfalah; Erpi Rahman; Ayi Srie Yuniawati (Journal of Business, Accounting and Finance, 2019)
This study aims to determine good corporate governance, going concern audit opinion, and the magnitude of the influence of good corporate governance on going concern audit opinion at the Regional Public Company (PERUMDA) Tirta Medal Sumedang. This study uses a descriptive research method approach with quantitative analysis techniques, conducted through a survey method. Data collection techniques were analyzed by means of observation and questionnaires. The population is SPI and Finance/Assets employees of PERUMDA Tirta Medal Sumedang as many as 30 people and the research sample is 30 people. The research data uses simple regression analysis, correlation test, coefficient of determination and hypothesis testing. The results showed that the implementation of good corporate governance was 2.360 (very good) with an average of 87.41 %, audit opinion going concern was 1.493 (good) with an average of 85.82%. at PERUMDA Tirta Medal Sumedang of 0.903, and the magnitude of the effect of service excellent on community satisfaction at PERUMDA Tirta Medal Sumedang of 82.94 % and there are 18.4% of other factors. The results of the calculation of the hypothesis, it turns out that tcount (14.68) > ttable (1.70113), it can be said that there is a positive influence between good corporate governance on going concern audit opinion at PERUMDA Tirta Medal Sumedang acceptable. Going concern audit opinion can be achieved and overcome with good corporate governance.